Does money matter in the ECB strategy? New evidence based on ECB communication - Helge Berger; Jakob de Haan; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2006)
We examine the role of money in the policies of the ECB, using introductory statements of the ECB President at the monthly press conferences during 1999-2004. Over time, the relative amount of words devoted to the monetary analysis has decreased. Our analysis of indicators of the monetary policy stance suggests that developments in the monetary sector, while somewhat more important in the later half of the sample, only played a minor role most of the time. Our estimates of ECB interest rate decisions suggest that the ECB's words (monetary-sector based policy intensions) are not an important determinant of its actions.
Keywords: E58; E52; E43; 330; ECB; communication; monetary policy; Geldpolitik; Publikationsanalyse; Staatliche Information; EU-Staaten